1428 Association Between Visceral Fat and Blood Pressure in Young Adolescents in Western India. (October 2012) - Nimbalkar, AS; Singh, SS; Singh, SR; Nimbalkar, SM
Abstract : Background and Aims: Risk of metabolic syndrome is 5 times higher in adolescents with more visceral fat deposition. We studied the association between visceral fat and blood pressure in young adolescents of gujarati ethnicity. Methods: 50 young healthy adolescents (age 17 to 21 years) of both genders from local community college participated in the cross-sectional non-experimental study. Omron Body Composition Monitor was used to quantify visceral fat level and visceral fat analysis. Height, Blood Pressure, Weight and other obesity parameters were measured. Results were expressed as mean±SD. Independent samples T test and Linear regression analysis was used. Results: Boys and Girls were equally recruited. No significant differences found between groups for pulse, diastolic pressure (DP) and visceral fat (VF) but differences between boys and girls for systolic pressure (SP), pulse pressure (PP) and mean arterial pressure (MAP) were present. Significant correlation between Visceral Fat (2.54+2.2) and Systolic Pressure (102.88+9.99), Diastolic Pressure (69+8.23), Mean Arterial Pressure (80.26+8.53) and Pulse Pressure (33.88+4.98) for females and between Visceral Fat (4.8+3.74) and Systolic Pressure (115.88+11.37), Mean Arterial Pressure (90.63+16.16) and Pulse Pressure (41.60+8.34) with the best correlation between Mean arterial Pressure and Visceral fat among males. Conclusion: Visceral obesity correlated with mean arterial pressure in both sexes with better correlation in males. Distribution of fat in the body is an important indicator which needs to be monitored and/or targeted in management of overweight and obese adolescents.